(untitled) (Global Journals of Research in Engineering, 2023)
This paper contains a production and inventory planning model with lot sizing in an RMG factory This model is an example of mixed integer linear programming The primary goal of this approach which combines the make-to-order MTO and make-to-stock MTS production methods are to simultaneously satisfy existing customer orders and new customer orders in order to reduce the total cost Here make-to-order MTO and make-to-stock MTS production systems are becoming more and more common since they allow businesses to increase revenues while managing expenses by maintaining a positive cash flow For mixed contexts where demand is cyclical but predictable and the model stores the predicted data and fresh forthcoming orders For the simulation creation of the model and output data were gathered from Samad Sweaters Ltd The concept is relevant to numerous production sectors including the textile apparel steel and food sectors As its main objective is to reduce costs through lot sizing industries that adopt this strategy can boost their profit margins while also keeping costs down Additionally it determines the cost of ordering and acquiring the raw materials Another strategy for reducing risk and raising revenue is to subcontract the order This is an alternative model option for completing an order by the delivery date